Teaching Arabic In Light Of The Competency Approach And Methods Of Teaching/ تعليمية اللغة العربية في ظل المقاربة بالكفاءات وطرق تدريسها - Messaoud Ouali; Abdelmonaim Benaouira (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The competency approach was among the essential pedagogies in learning in its various ways through the employment of modern linguistic and pedagogical theories that would contribute to a sound basis for building a linguistic faculty for the learner at all stages of learning, thus raising the level of the Arabic language. This study aims to highlight the role and contributions of the approach to educational competence and its teaching methods in the field of teaching Arabic, as it is a pioneering and widely used approach in many countries through its vision of the learner and its teaching methods, and attention to it on the basis that it is the center of learning and that the rest of the elements serve his interest to achieve education goals. This study used the descriptive analytical approach, which aims to collect data with accurate scientific descriptions of the study in its current report, relied on analyzing the content of a valuable group of references that dealt with the subject of teaching the Arabic language according to the competency approach, through balancing and comparing the references approved in the study. This made us believe that the competency approach is essential in learning and teaching the Arabic language. The study found that there are many different teaching methods according to this approach: the project teaching method, the cooperative learning method, the strategic learning method, and the problem-solving method, which makes the role of the teacher direct, monitoring, and forming rather than memorizing, which contribute effectively to learning the Arabic language and that these methods can be combined to obtain an effective way according to the educational situation and learning objectives.